Exercise Intervention in Treatment of Neuropsychological Diseases: A Review - Chen, Zichao; Lan, Wencen; Yang, Guifen; Li, Yan; Ji, Xiang; Chen, Lan; Zhou, Yan; Li, Shanshan (Frontiers in Psychology, 2020)
Abstract Faced with a constant inundation of information and increasing pressures brought by the continuous development of modern civilization, people are increasingly faced with mental health challenges that are only now being actively researched. Mental illness is caused by brain dysfunction due to internal and external pathogenic factors that destroy the integrity of the human brain and alter its function. Regular participation in physical exercise can stimulate the cerebral cortex and simultaneously increase supply of oxygen and nutrients, helping to preserve or restore normal functioning of the nervous system. In conjunction with other systems of the body, the nervous system constitutes the neuro-humoral regulation system responsible for maintaining the stable state of the human body. This paper is a systematic review of studies investigating effects of exercise intervention on several common neuropsychological diseases, including depression, anxiety disorder, autism, and attention-deficit/hyperactivity disorder. Furthermore, we discuss possible physiological mechanisms underlying exercise-induced benefits and study limitations that must be addressed by future research. In many cases, drug therapy is ineffective and brings unwanted side effects. Based on the literature, we conclude that exercise intervention plays a positive role and certain standards must be established in the field to make physical activity consistently effective.